Legalisasi Nikah Siri Melalui Isbat Nikah (Studi Analisis Terhadap Penetapan Pengadilan Agama Pandan) - Bincar Halomoan Siregar Bincar (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
The purpose of the study was to determine the judge's considerations in determining the law of marriage isbat against unregistered marriage in the Pandan Religious Court. The type of research used is qualitative research with a normative legal approach. Normative research is a process to find a rule of law, various legal principles, and legal doctrines in order to answer the legal issues faced. Data collection techniques are by means of observation, interviews, and literature review. and documentation. Data analysis techniques include data reduction, data presentation and conclusion drawing. Data reduction means summarizing, choosing the main things, focusing on the important things, looking for themes and patterns. The presentation of the data is done in the form of a short description (narrative), charts, relationships between categories and the like. Through the presentation of data, the data is organized, arranged in a relationship pattern, so that it will be easy to understand and draw conclusions. The results of the study show that the factors causing the occurrence of unregistered marriages which are involved in the jurisdiction of the Pandan Religious Court are not having fees, lack of administration and not getting the blessing of the guardian. Meanwhile, according to the Khazanah Fiqh School, unregistered marriages are legal, if the pillars and conditions of marriage are fulfilled and according to the Compilation of Islamic Law, unregistered marriages are invalid, because they are not recorded by official officials, so that the marriage is valid it must be registered with the Religious Court and the judge accepts it. if the judge rejects it, then the marriage is invalid.